One-year results following PASCAL-based or MitraClip-based mitral valve transcatheter edge-to-edge repair - Geis, Nicolas; Schlegel, Philipp; Heckmann, Markus B.; Katus, Hugo; Frey, Norbert; Crespo López, Patricia; Raake, Philip (ESC heart failure, 2022)
Aims Mitral valve transcatheter edge-to-edge repair (TEER) has been established as a suitable alternative to mitral valve surgery in patients with severe mitral regurgitation (MR) and high surgical risk. The PASCAL system represents a novel device, potentially augmenting the toolkit for TEER. The aim of this study was to assess and compare short and 1 year safety and efficacy of the PASCAL and MitraClip systems for TEER. Methods and results Procedural, short, and 1 year outcomes of a 1:2 propensity-matched cohort including 41 PASCAL and 82 MitraClip cases were investigated. Matching was based on clinical, laboratory, echocardiographic, and functional characteristics. The primary endpoints assessed were procedural success [as defined by the Mitral Valve Academy Research Consortium (MVARC)], residual MR, functional class, and a composite endpoint comprising death, heart failure hospitalization, and mitral valve re-intervention. We found for the PASCAL and the matched MitraClip cohort no significant differences in MVARC defined technical (90.2% vs. 95.1%, P = 0.44), device (90.2% vs. 89.0%, P = 1.0), or procedural (87.8% vs. 80.5%, P = 0.45) success rates. Accordingly, the overall MR reduction and improvement in New York Heart Association (NYHA) class were comparable (1 year follow-up: MR ≤ 2 95% vs. 93.6%, P = 1.0; NYHA ≤ 2 57.1% vs. 66.7%, P = 0.59). The composite outcome revealed no statistically significant difference between both devices (1 year follow-up: 31.7% vs. 37.8%, P = 0.55). Interestingly, we found at both short and 1 year follow-up a significantly higher rate of patients with none or trace MR in the PASCAL-treated cohort (short follow-up: 17.9% vs. 0%, P = 0.0081; 1 year follow-up: 25% vs. 0%, P = 0.0016). Conversely, the rate of aborted device implantations due to an elevated transmitral gradient was higher in PASCAL interventions (9.8% vs. 1.2%, P = 0.04). Conclusions Transcatheter edge-to-edge repair using the PASCAL or MitraClip device results in favourable and comparable outcomes regarding safety, efficacy, and clinical improvement after 1 year.
Gesehen am 30.11.2022